0178 Simulated and anticipatory frontline education quality improvement project (SAFEQIP). (2nd November 2015) - Macgloin, Helen; Lofton, Lydia; Lentaigne, Julian; Korb, Cecilia; Desai, Ajay; Lane, Mary; Burmester, Margarita
Abstract : Background: The benefits of education through simulation are augmented when coupled to quality improvement and educational initiatives by improving patient safety. 1 We harnessed the strengths of simulation to develop a quality improvement project (SAFEQIP) aiming to improve anticipatory care, using role allocation through a multifaceted educational approach with the overarching goal to improve patient safety, staff education and team-working. Methodology planned: In-situ Simulated inter-PRofessional Team (SPRinT) courses are embedded within PICU. Currently, a validated tool monitors participant self-evaluation of team-performance during these SPRinT courses, and during real resuscitations. 2, 3 The project will involve pre-allocation of roles during SPRinT courses, and role allocation during twice daily safety huddles of the arrest team, thereby providing roles prior to real and simulated arrests. A change in TeamMonitor 2 scores and process measures will be assessed pre and post project implementation. Additionally a system has been created to disseminate learning events and latent threats from simulations to the wider team whilst ensuring a confidential, safe learning environment. This will also enable replication of successes by sharing and cascading Safety 2 events to frontline staff. Outcomes anticipated/to date: Team-performance including role allocation has been scored by participating staff during real resuscitations since May 2014. Additional baseline data suggests most role allocation is performed during the arrest with no current pre-planning in place. Staff desire for anticipatory planning was strongly suggested from feedback from simulated and real events. Potential impact: SAFEQIP could mitigate threats associated with ad-hoc team-building during resuscitations.Staff will be empowered to strategically plan prior to resuscitations and team-cohesiveness fostered. Learning is facilitated through sharing learning events. Patient outcome may benefit as pre-planning enables less hands-off time during chest compressions, decreased time to initiate crucial first treatments and improved leadership and communication. 4 References: Barton J, et al . Impact of multidisciplinary team training and high fidelity simulation in critical patient scenarios. Med Sci Educ 2013;23 (3S):532–540 Stocker M, et al . Reliability of team-based self-monitoring in critical events: a pilot study. BMC Emerg Med 2013;13:22 Stocker M, et al . Impact of an embedded simulation team training programme in a paediatric intensive care unit: a prospective, single-centre, longitudinal study. Intensive Care Med. 2012;38(1):99–104 Fernandez Castelao E, et al . Effects of team coordination during cardiopulmonary resuscitation: a systematic review of the literature. J Crit Care 2013;28:504–521